Rekontruksi Industrialisasi Guna Mewujudkan Kemandirian Indonesia - Sardjono, Sigit (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
In the globalization era nowadays, the increase of interdependence among the states becomes unavoidable. But, this dependence has to be minimized a little by little. It makes what to do limited. The imported product dependence makes goods price more expensive. Meanwhile, the map of economy and business world atmosphere is colored with increasingly higher competence. All of them effect no option for us, except increase ability and superiority of all national economic potency in order to achieve the continuous national development. In welcoming the commitment explanation, it is time to reinforce the strategy for building the industry sector by featuring our own strength to increase independence in implementing the national development. It can especially be personified by eliminating the problems in the sector. The most important thing is also to increase nationalism sense. The new nationalism is not chauvinism and isolated nationalism, but nationalism for domestic product appreciation rather than imported product. Although the action for constructing industrialization is slow, but it is better to be late than not at all.Â Keywords:Â  Industrial, Development, Oligopoly, Nasionalism